Short Communication: Assessment of genetic diversity in Lai (Durio kutejensis) local cultivars of Batuah (Indonesia) using ISSR marker - FITRI HANDAYANI; SRIWULAN PAMUJI RAHAYU (Biodiversitas Journal of Biological Diversity, 2017)
Handayani F, Rahayu SP. 2017. Assessment of genetic diversity in Lai (Durio kutejensis) local cultivars of Batuah (Indonesia) using ISSR marker. Biodiversitas 18: 525-529. Lai is an indigenous germplasm of Kalimantan which has potency to be developed as superior tropical fruit. Lai has attractive flesh color from yellow to reddish orange which represents the high content of carotene with smooth aroma or odorless fruit, and fruit storage period which longer than durian. Unfortunately, nowadays there is limited scientific information about its genetic diversity as important basic information for genetic conservation and breeding program. Batuah village in Kutai Kartanegara District is one of the center of origin and center of diversity of Lai in East Kalimantan, Indonesia which has many local cultivars with superior traits. The aim of this research was to study the genetic diversity of eight Lai local cultivars of Batuah village using molecular marker of ISSR. The total genomic DNA of eight Lai cultivars was isolated and was then used as template in the PCR amplification reaction using 10 ISSR primers. The result shows that similarity coefficient of eight Lai cultivars ranged between 0,34 and 0,58. Seven cultivars were grouped in the same cluster with 0,44 of similarity coefficient, while Lai Durian was separated in 0,34 of similarity coefficient. Genetically, the most similar existing cultivars are Lai Kuning and Lai Belimbing with the similarity coefficient of 0,58.